The oncoprotein v-Myb activates transcription of Gremlin 2 during in vitro differentiation of the chicken neural crest to melanoblasts - Starostová, Michaela; Cermák, Vladimír; Dvořáková, Marta; Karafiát, Vít; Kosla, Jan; Dvořák, Michal (Gene, 2014)
The neural crest (NC) is a transient dynamic structure of ectodermal origin, found in early vertebrate embryos. The multipotential NC cells migrate along well defined routes, differentiate to various cell types including melanocytes and participate in the formation of various permanent tissues. As there is only limited information about the molecular mechanisms controlling early events in melanocyte specification and development, we exploited the AMV v-Myb transcriptional regulator, which directs differentiation of in vitro chicken NC cells to the melanocyte lineage. This activity is strictly dependent on v-Myb specifically binding to the Myb recognition DNA element (MRE). The two tamoxifen-inducible v-Myb alleles were constructed one which recognizes the MRE and one which does not. These were activated in ex ovo NC cells, and the expression profiles of resulting cells were analyzed using Affymetrix microarrays and RT-PCR. These approaches revealed up-regulation of the BMP antagonist Gremlin 2 mRNA, and down-regulation of mRNAs encoding several epithelial genes including KRT19 as very early events following the activation of melanocyte differentiation by v-Myb. The enforced v-Myb expression in neural tubes of chicken embryos resulted in detectable presence of Gremlin 2 mRNA. However, expression of Gremlin 2 in NC cells did not promote formation of melanocytes suggesting that Gremlin 2 is not the master regulator of melanocytic differentiation.
Keywords: kuřecí embryo; Oligonucleotide Array Sequence Analysis; melanocyty; alely; Cells, Cultured; Cell Differentiation; onkogenní proteiny v-myb; zvířata; v-Myb-dependent genes; aktivace transkripce; keratin-19; regulace genové exprese; Gene Expression Regulation; Intercellular Signaling Peptides and Proteins; Avian Proteins; KRT19; Melanocyte development; transkriptom; Tamoxifen-inducible v-Myb; Transcriptional Activation; Melanocytes; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; kultivované buňky; Chick Embryo; mezibuněčné signální peptidy a proteiny; Animals; PRDC; crista neuralis; ptačí proteiny; Keratin-19; Transcriptome; kostní morfogenetický protein 5; Neural Crest; buněčná diferenciace; Oncogene Proteins v-myb; Bone Morphogenetic Protein 5; Alleles